2018
DOI: 10.1371/journal.pone.0205180
|View full text |Cite
|
Sign up to set email alerts
|

A type 2 diabetes disease module with a high collective influence for Cdk2 and PTPLAD1 is localized in endosomes

Abstract: Despite the identification of many susceptibility genes our knowledge of the underlying mechanisms responsible for complex disease remains limited. Here, we identified a type 2 diabetes disease module in endosomes, and validate it for functional relevance on selected nodes. Using hepatic Golgi/endosomes fractions, we established a proteome of insulin receptor-containing endosomes that allowed the study of physical protein interaction networks on a type 2 diabetes background. The resulting collated network is f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 85 publications
(131 reference statements)
0
23
0
Order By: Relevance
“…2). Of interest, the T2D-protomodule functional specialization expands in IREN (to include cell cycle, trafficking, signaling components, reactive oxygen species components) [33]. “Hub bottlenicity” (also named centrality) is also thought to dictate essentiality and constitutes the dynamic component of a regulated network [34], [35].…”
Section: The Endosomal Ir Protein-proteins Interaction Network (Ppin)mentioning
confidence: 99%
See 3 more Smart Citations
“…2). Of interest, the T2D-protomodule functional specialization expands in IREN (to include cell cycle, trafficking, signaling components, reactive oxygen species components) [33]. “Hub bottlenicity” (also named centrality) is also thought to dictate essentiality and constitutes the dynamic component of a regulated network [34], [35].…”
Section: The Endosomal Ir Protein-proteins Interaction Network (Ppin)mentioning
confidence: 99%
“…Cdk2, which displays the highest centrality and is a high-confidence candidate associated with T2D genetic risk, indeed readily associates with key elements including the IR, PTPLAD1, Rab5c, tubulin and actin cytoskeletons all containing appropriate phosphorylation sites. In such a network, PTPLAD1, in the same incoherent input, controls IR tyrosine phosphorylation and other key interactions [33] (Fig. 2).…”
Section: The Endosomal Ir Protein-proteins Interaction Network (Ppin)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2007, the first diseasome constructed by the mathematician Albert Barabasi from the Online Mendelian Inheritance in Man database (OMIM) showed that T2D occupies a central hub [21]. In 2018, the first T2D physical protein-protein interactions network (PPIN), constructed from validated variants, termed diabetes protomodule, displayed the proteins' hepatic nuclear factors HNF4A and HNF1A as central nodes [22] (Figure 2). The HNF1A variant identified by whole-exome sequencing in a homogeneous Latino cohort is an example of a rare variant with a high causality at a population level [23].…”
Section: Introductionmentioning
confidence: 99%